2018
DOI: 10.1111/jdi.12948
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of myocardial glucose uptake with facilitated myocardial glucose transporter 4 translocation contributes to alleviation of diabetic cardiomyopathy in rats after duodenal‐jejunal bypass

Abstract: Aims/Introduction Duodenal‐jejunal bypass ( DJB ) surgery has been reported to effectively relieve diabetic cardiomyopathy ( DCM ). However, the specific mechanisms remain largely unknown. The present study was designed to determine the alterations of myocardial glucose uptake ( MGU ) after DJB and their effects on DCM . Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…PKM1/2 is involved in glycolysis, which is closely related to the occurrence of diabetes 34,35 . GLUT4 is a glucose carrier/transporter located on the cell membrane 36 . A number of literature have reported that the increase of GLUT4 expression promotes the uptake and utilization of glucose by cells, thereby playing an integral role in the treatment of diabetes 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…PKM1/2 is involved in glycolysis, which is closely related to the occurrence of diabetes 34,35 . GLUT4 is a glucose carrier/transporter located on the cell membrane 36 . A number of literature have reported that the increase of GLUT4 expression promotes the uptake and utilization of glucose by cells, thereby playing an integral role in the treatment of diabetes 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on basic mechanistic research of BS. In diabetic rats, the restoration of myocardial glucose uptake alleviates diabetic cardiomyopathy after duodenal-jejunal bypass surgery through facilitating myocardial glucose transporter (GLUT; GLUT1 and GLUT4) translocation 15 . Although BS can treat morbid obesity, until the mechanism can be clarified, we imagine that the beneficial effects of surgical treatment could also be achieved through non-surgical devices.…”
Section: Mechanism Of Obesity and Metsmentioning
confidence: 99%
“…Under normal physiological conditions, glucose transporter-4 (GLUT-4), an intracellular protein, is translocated to the cell membrane in response to insulin, where it facilitates glucose uptake and utilization [48,49]. However, in diabetes, the expression and function of GLUT-4 are compromised, leading to a marked reduction in glucose transport and impaired energy utilization in the myocardium [50]. However, many studies have reported that moderate exercise can reverse these effects by increasing GLUT-4 expression and glucose transport, thereby activating the pyruvate dehydrogenase complex [51].…”
Section: Cardiac Cell Metabolismmentioning
confidence: 99%